E Pengaruh Waktu Fermentasi Nanas (Ananas comosus L) Terhadap Mutu Fisik Es Krim Sinbiotik Tempe : Pengaruh Waktu Fermentasi Nanas (Ananas comosus L) terhadap Mutu Fisik Es Krim Sinbiotik Tempe - Ambar Fidyasari, STP., MP; Fitri Eka Lestari; Wahyu Maslukah (Amerta Nutrition, 2022)
Background: Modifications of ice cream made by adding probiotics and prebiotics as its constituent components known as symbiotic ice cream Pineapple juice is fermented with commercial probiotics containing L. Casei. The length of fermentation can affect the quality of the resulting product. Objectives: This experiment aims to determine the physical quality of symbiotic ice cream containing pineapple fermentation and tempe with various fermentation length time Methods: This research was conducted with experimental design (complete randomized), This research was done   in three steps, making pineapple juice, then carried out a fermentation process for 12 hours, 24 hours, 48 hours, then making synbiotic ice cream and testing physical quality including organoleptic (color, aroma, taste and texture), overrun, viscosity and pH.  One Way Anova test and following by Duncan.used to analyzed the data. Results: It showed that the 12-hour overrun was 31.25, the viscosity was 4.23cP and the pH was 5.50; 24 hours overrun 27.08, viscosity 5.84cP and pH 5.44; 48 hours overrun 16.67, viscosity 8.91cP and pH 5.30. Conclusions: It was concluded that the physical quality analysis of overrun, viscosity and pH showed that the length of fermentation time had an effect of tempe synbiotic ice cream on its physical quality.